Nuclear localizaiton of β-catenin is associated with poor survival and chemo-/radioresistance in human cervical squamous cell cancer - Zhang, Yanna (e-Century Publishing Corporation, 2014)
Nuclear expression of β-catenin has been suggested as an independent prognostic marker in a variety of cancers. The objective of this study was to investigate the clinicopathologic significance of nuclear β-catenin expression in patients with cervical squamous cell carcinoma (CSCC). In this original research article, we detected nuclear β-catenin expression in 29/171 CSCC tissues (17.0%). Patients without nuclear β-catenin expression had a significantly better outcome than patients with nuclear β-catenin expression (93.7% versus 82.7% P = 0.027). Furthermore, nuclear β-catenin expression was predictive of prognosis in CSCC patients with early stage disease (FIGO stage I or tumor size ≤ 4 cm), with well/moderately differentiated tumors, or lymph node metastasis. Interestingly, nuclear β-catenin expression correlated with poor outcome in patients who received postoperative chemotherapy or radiotherapy. Multivariate analysis suggested that nuclear β-catenin expression is an independent prognostic indicator in CSCC. Our findings suggest that nuclear β-catenin expression may be used as a prognostic biomarker in CSCC, especially for patients with early stage disease, well/moderately differentiated tumors, or lymph node metastasis. Moreover, nuclear β-catenin expression has potential as a predictive marker of chemoresistance and radioresistance in CSCC.